Management of Seed Associated Fungi and Alternaria Leaf Spot Disease of Black Mustard (Brassica Nigra L.) Using Botanicals (Bangladesh Journal of Agricultural Research, 2023)
The efficacy of five native botanicals viz., neem, castor, akondo, basok and ata against the seed associated fungi and in controlling the leaf spot disease of black mustard was evaluated. In blotter method, maximum reduction (85.91%) of seed associated fungi was observed in the seeds treated with ata (1:1) while neem (1:1), ata (1:2) and castor (1:1) gave 83.52, 82.59 and 82.39%, respectively reduction of fungi over control. Maximum seed germination (93%) was observed in seeds treated with akondo (1:1), where neem (1:1), castor (1:1) and akondo (1:2) supported 92, 92 and 90% seed germination, respectively. Maximum reduction of percent disease incidence (29.22%) and percent diseases severity (24.67%) were recorded with the application of neem (1:1) at 28 days after sowing with highest shoot length (16.09cm), root length (4.69cm), vigor index (1842.56%) and seed yield (33.70%) comparison to control in the net house. The findings neem (1:1) was found as an effective botanical for the ecofriendly management of seed associated fungi and Alternaria leaf spot diseases of black mustard.Bangladesh J. Agril. Res. 46(4): 407-416, December 2021